Tumor Differentiation is Correlated with Estrogen Receptor Beta (ERβ) Expression but Not with Interleukin-6 (IL-6) Expression in Colorectal Carcinoma - Theodora, Imelda; Sudiana, I Ketut; Budipramana, Vicky Sumarki; Erwin, Ferdinand; Dewi, Sianty; Novita, Bernadette Dian (The Indonesian Biomedical Journal, 2024)
BACKGROUND: Colorectal carcinoma (CRC), the third most common malignant disease worldwide, is associated with estrogen receptor β (ERβ) and interleukin-6 (IL-6). ERβ is known to down-regulate IL-6 in prostate cancer, lung carcinoma, and CRC cell lines; however, its effect on human with CRC remains unclear. Therefore, this study was conducted to investigate the association between ERβ and IL-6 expressions with the clinicopathological features of CRC.METHODS: This was an analytic observational study using 40 paraffin blocks of CRC patients. ERβ and IL-6 expression was measured by immunohistochemistry (IHC) staining. The percentage of immunoreactive tumor cell per 1000 cells was manually recorded and tumor differentiation as well as tumor infiltration were determined. Tumor differentiation was graded according to the World Health Organization (WHO) 2010 criteria, while tumor infiltration was defined based on the American Joint Committee on Cancer (AJCC) 8th edition.RESULTS: Fifty percent of samples were well-differentiated CRC, and 57.5% samples were T3 infiltration tumors. IHC staining showed 35.5% of samples were positive for ERβ expression, while 70.86% were positive for IL-6 expression. There were negative correlation of ERβ expression with tumor differentiation (p=0.018; r=-0.371), but no correlation with tumor infiltration (p=0.836) were found. There was no correlation between ERβ expression with IL-6 expression (p=0.154).CONCLUSION: There is statistically significant correlation between tumor differentiation and ERβ expression, wherein improved tumor differentiation is linked to higher levels of positive ERβ expression. However, there is no discernible relationship between IL-6 and tumor differentiation. These findings suggest that while IL-6 was involved in the growth of the tumor, ERβ expression might have an impact on tumor differentiation.KEYWORDS: colorectal carcinoma, estrogen receptor beta, interleukin-6, cell differentiation